Transthyretin is involved in depression-like behaviour and exploratory activity - Sousa, João Carlos (2004)
Transthyretin (TTR), the major transporter of thyroid hormones and vitamin A in cerebrospinal fluid (CSF), binds the Alzheimer β-peptide and thus might confer protection against neurodegeneration. In addition, altered TTR levels have been described in the CSF of patients with psychiatric disorders, yet its function in the CNS is far from understood. To determine the role of TTR in behaviour we evaluated the performance of TTR-null mice in standardized tasks described to assess depression, exploratory activity and anxiety. We show that the absence of TTR is associated with increased exploratory activity and reduced signs of depressive-like behaviour. In order to investigate the mechanism underlying these alterations, we measured the levels of cathecolamines. We found that the levels of noradrenaline were significantly increased in the limbic forebrain of TTR-null mice. This report represents the first clear indication that TTR plays a role in behaviour, probably by modulation of the noradrenergic system.